Penyuluhan Regulasi dan Aturan Penggunaan Harta Waris dalam Hukum Islam Pada Kelompok Nasabah Prioritas Bank Rakyat Indonesia - Tiena Masriani, Yulies (Universitas 17 Agustus 1945 Semarang, 2024)
Indonesia, as a rule-of-law state (rechstaat), regulates the life of the nation and state based on law, as reflected in the provisions of civil law that govern relationships between individuals, including matters of inheritance. Inheritance distribution in Indonesia follows various legal systems, such as Islamic inheritance law, civil inheritance law, and customary law, each with different principles and rules. Inherited assets include a wide range of properties, such as movable and immovable assets, property rights, debts, money, businesses, and wills. In practice, the distribution of inheritance in Indonesia often involves an administrative process requiring a Certificate of Inheritance Rights (Surat Keterangan Hak Waris or SKHW) to verify who is entitled to inherit and the share each heir is entitled to receive. This study aims to educate the public, particularly customers of Bank Rakyat Indonesia, about inheritance law and the procedures involved. Additionally, the research highlights the crucial role of notaries as Land Deed Officials (Pejabat Pembuat Akta Tanah, PPAT) in the legalisation of inheritance ownership, particularly concerning the management of land certificates and other legal documents. Through community service conducted at the Bank Rakyat Indonesia (BRI) branch in Central Semarang, this study educates the public on inheritance rights and the role of notaries in ensuring the legal validity of inheritance distribution in accordance with applicable laws. Indonesia's plural inheritance law system provides flexibility in choosing the applicable legal system, whether Islamic law, civil law, or customary law. In the case of disputes, notaries play a role in resolving conflicts by creating peace agreements, cancellation deeds, or waivers of claim deeds. This study is expected to help the public better understand inheritance law and the role of notaries in ensuring that inheritance rights are distributed fairly and legally in accordance with the prevailing laws.